Scope of seecuve Conservative Management in Penetrating Abdominal Injury (Journal of Surgical Sciences, 2020)
Introduction: Now-a-days penetrating trauma is increasing because of increased incidence of violence in our society and a large number of these patients present in trauma centers with normal vital signs and negative abdominal examination. Historically operative management was the main approach for penetrating abdominal trauma, but in recent time non operative management is also gaining popularity.Objective: This study was aimed to observe the scope of non-operative management of penetrating abdominal injury in a tertiary level hospital of Bangladesh.Methods: 54 patients of penetrating abdominal injury were selected from the casualty department of Dhaka Medical College Hospital. Data were collected from these patients by a preformed questionnaire and finally the data were analyzed by SPSS 16.Results: Among the 54 patients only 9 required exploration, where generalized peritonitis was the major cause of operation and the common organ found to be injured was small intestine.Conclusion: Selective non-operative approach may be considered for patients with penetrating abdominal injury, provided that sufficient man power and expertise are available.Journal of Surgical Sciences (2018) Vol. 22 (1): 58-61